The Problem of Defining a Riddle - Zokirova Sohiba Mukhtoraliyevna; Kholikova Mukhtasar Kurbonali qizi (Zien Journals, 2023)
Problems of the categorical organization of crossword puzzles, we have established the specifics of this genre, which is manifested in its discursive integrity - bringing the author's intention in line with the performance of tasks by the addressee; in hypertext, megatext and graphic connectivity; in the wide information content generated by the consciousness of the author of the crossword puzzle, fixed in tasks and appealing to the consciousness of the addressee, his competence and interpreter; in a special anthropocentricity, realized at the turn of two consciousnesses by an irrelevant addresser, a program of addressing a hypothetical addressee and a real addressee.
Keywords: enigmat; hypertext; megatext; graphic connectivity